Distribution of electric field in medium voltage cable joint geometry - Illias, Hazlee Azil; Lee, Z.H.; Bakar, A.H.A.; Mokhlis, Hazlie; Ariffin, A.M. (2012)
Cable joint is used to connect different sections of cable because a cable section is limited to a certain length. The design of a cable joint mainly depends on the cable type, the applied voltage and the cores. These factors contribute to the way of how electric field stress is distributed at the cable joint. If there are defects exist within the cable joint insulation material, the electric field at that region is altered. The alteration may cause electrical discharges to occur within the defects if the electric field magnitude is larger than the breakdown strength at the defect sites. Therefore, this paper investigates the electric field distribution in a medium voltage cable joint in the presence of defects. The investigation was done through modelling a medium voltage (MV) cable joint using finite element analysis (FEA) software. Several parameters such as the defect size and location, insulation material dielectric constant and insulation thickness have been studied of their effects on the electric field distribution at the cable joint. The results obtained may be able to help in the designing of cable joint structures which can reduce the electric field stress.